Development of the RP-HPLC Method for Simultaneous Determination and Quantification of Artemether and Lumefantrine in Fixed-Dose Combination Pharmaceutical Dosage Forms - Simon Nyarko; Kwabena Ofori-Kwakye; Raphael Johnson; Noble Kuntworbe; Desmond Asamoah Bruce Otu; Denis Dekugmen Yar; Yaa Asantewaa Osei (Advances in Pharmacological and Pharmaceutical Sciences)
Developing countries face enormous challenges with substandard and falsified antimalarial drugs. One specific issue is the lack of a simple, cost-effective, and robust HPLC method to simultaneously determine and quantify the active pharmaceutical ingredients (APIs) in fixed-dose artemether-lumefantrine pharmaceutical dosage forms. The current study developed a novel, simple, sensitive, precise, accurate, and cost-effective RP-HPLC method for the simultaneous determination and quantification of artemether and lumefantrine in pharmaceutical dosage forms. The HPLC analysis was carried out on an Agilent 1260 Infinity Series HPLC system equipped with an ODS Intersil-C8 (150 × 4.6 mm) 5.0 µm column, by isocratic elution. The mobile phase composition consisted of acetonitrile and 0.05% orthophosphoric acid buffer of pH 3.5 in the ratio of 70 : 30 v/v. The analysis was performed at a 1 mL/min flow rate and a column temperature of 25°C. The total run time was 6 minutes. The detection was done with a variable wavelength detector (VWD) at an isosbestic point wavelength (λ) of 210 nm. The developed method was validated according to the ICH guidelines concerning system suitability, specificity, linearity, accuracy, precision, and robustness. The system suitability of the developed method revealed satisfactory theoretical plates and symmetry factors. The method proved to be specific, with no interference of mobile phase or excipients. The calibration plot exhibited linearity over the concentration range of 275–1925 μg/mL with R2 = 0.9992 for artemether and a range of 150–1050 μg/mL with R2 = 0.9985 for lumefantrine. The accuracy of the method, determined by the recovery study, was 99.79–100.16% for artemether and 99.04–99.50% for lumefantrine. The % RSD values for intraday precision were 0.175 and 0.203, while interday precision values were 0.340 and 0.554 for artemether and lumefantrine, respectively. The method demonstrated robustness when subjected to slight modifications in the flow rate, column temperature, and mobile phase composition. The developed analytical method proved satisfactory as per ICH guidelines and hence can be used for the determination and quantification of artemether and lumefantrine in bulk drug and pharmaceutical dosage forms.